Illocutionary Acts Found in Comic Strips Written by Eleventh Grade of Senior High School Students - Gustiani, Tia; Roza, Veni (BiCED Proceeding, 2024)
The objective of this research was to figure out illocutionary acts found in comic strips. This research was a qualitative research. The data of this research were obtained from comic strips written by senior high school students. This research was conducted at SMAN Agam Cendekia. The population of this research was eleventh grade students of SMAN Agam Cendekia. The researchers found 11 illocutionary acts in total. In detail, there were 6 representative, 4 directive, and 1 commissive illocutionary act. The results implied that eleventh-grade students at SMAN Agam Cendekia tend to focus on conveying information and directing actions through their comic strip dialogues, as indicated by the predominance of representative and directive illocutionary acts. This suggests that the students’ primary goal was to communicate ideas, facts, or beliefs and to influence or guide the behavior of the characters. The relatively low occurrence of commissive and the absence of expressive acts might indicate a less frequent use of promises, commitments, or emotional expressions in their narratives. This could reflect the students' narrative style, which emphasizes action and information over emotional depth or future commitments. Overall, the study highlights the linguistic choices made by the students in constructing meaning and interactions in their comic strips.